AN ANALYSIS OF POLITENESS STRATEGIES USED BY THE CHARACTERS IN THE BLIND SIDE MOVIE - Suryani, Christina; Sada, Clarry; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The aim of this study was to find out what politeness strategies are implemented by the characters in the context of various role relationship in The Blind Side movie and the contexts that affect the choice of politeness strategies used by the characters. In this research, the researcher used the theory of politeness strategies proposed by Brown and Levinson (1987) and the Ethnography of Speaking proposed by Dell Hymes (1964). The method of this research was qualitative research. Through the transcript of The Blind Side movie, observation and note taking, the data was collected. The subject of the research was ten characters in The Blind Side movie who have various role relationships. The research was done by observing and analysing the contexts used by the characters, then based on the contexts the researcher interpret what politeness strategies used by the characters in The Blind Side movie. It can be concluded that there were four politeness strategies applied by the characters, they were Balad on Record strategy, Negative Politeness strategy, Off-Record strategy and Positive Politeness strategy. Furthermore, there were four contexts of situation affect the characters in choosing the politeness strategy. The four contexts were participants, ends, settings and keys.Â Keywords: Characters, Politeness Strategies, The Blind Side